Winter soldier, Iraq and Afghanistan eyewitness accounts of the occupations (Haymarket Books, 2008)
"In spring 2008, Iraq Veterans Against the War gathered outside Washington, D.C., and testified to atrocities they personally committed or witnessed while deployed in the occupations of Afghanistan and Iraq. In this book are the powerful words, images, and documents of this historic event." "Winter Soldier: Iraq and Afghanistan preserves and honors the participants' courageous contributions in order to ensure that people around the world remember their stories and struggles. The book's documentation includes the testimonies of dozens of veterans addressing such issues as the U.S. military's callous disregard for civilian life, the torture of detainees, the culture of racism that's inherent in a military occupation, gender discrimination, and the health crisis facing today's veterans."--BOOK JACKET.